2013
DOI: 10.5114/aoms.2013.33177
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial rotavirus gastroenterocolitis in a large tertiary paediatric hospital in Warsaw, 2006-2010

Abstract: IntroductionRotaviruses are the leading cause of community-acquired and nosocomial gastroenterocolitis in children. There are limited data concerning the epidemiology of nosocomial rotavirus gastroenterocolitis (NRVG) in Central European countries, including Poland. The aim of our study was to analyse the epidemiology of NRVG in a large tertiary hospital in Warsaw.Material and methodsWe analysed retrospectively data of 63 173 patients aged 0-18 years hospitalized in the period 2006-2010. Nosocomial rotavirus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
2
5
0
3
Order By: Relevance
“…Studies have shown that rotavirus gastroenteritis is more frequent in the autumn and winter months [16,17]. Similarly, we found that rotavirus gastroenteritis was more frequent (77.5%) between October and March.…”
Section: Discussionsupporting
confidence: 66%
“…Studies have shown that rotavirus gastroenteritis is more frequent in the autumn and winter months [16,17]. Similarly, we found that rotavirus gastroenteritis was more frequent (77.5%) between October and March.…”
Section: Discussionsupporting
confidence: 66%
“…(13) çalışmasında ise ishal nedeniyle hastaneye yatırılarak tedavi altına alınan çocukların %34.4'ü, Nitsch-Osuch ve ark. (15) çalışmalarında ise %24'ü rotavirüs enteriti tanısıyla yatış yapılan hastalardan oluştuğu raporlanmıştır. Avrupa'da yapılan ve birçok ülkeyi içine alan çalışmada ishalli çocuklarda rotavirüs pozitifliği %27-52 olarak belirtilmiştir (16) İshalli hastaların tedavisinde özellikle sosyo-ekonomik seviyesi düşük bölgelerde ishal şiddetinin azaltılması için çinko ve probiyotik tedavileri tercih edilmektedir (2).…”
Section: Discussionunclassified
“…Yatarak tedavi altına alınan hastalarda enterik adenovirüs sıklığı ise literatürle uyumludur. Rota ve enterik adenovirüs ishal tanısı literatürle uyumlu olarak erkek cinsiyette daha sık görülmüştür (15,17).…”
Section: Discussionunclassified
“…In the setting of transplantation, it is possible that the virus is transmitted from infected children or healthcare workers to organ transplant patients during an outbreak, since rotavirus easily presents with nosocomial infection . Indeed, hospitalization and frequent hospital visiting may be important risk factors . Overall, the incidence of rotavirus infection in transplantation setting is considerably high according to these reported cohort studies (Table ).…”
Section: Introductionmentioning
confidence: 95%
“…Fecal‐oral infection is the most common transmission route and poor hygiene accounts for spreading of the virus among children in developing world . In the setting of transplantation, it is possible that the virus is transmitted from infected children or healthcare workers to organ transplant patients during an outbreak, since rotavirus easily presents with nosocomial infection . Indeed, hospitalization and frequent hospital visiting may be important risk factors .…”
Section: Introductionmentioning
confidence: 99%